World Economic Outlook, October 2019 : Global Manufacturing Downturn, Rising Trade Barriers. (World Economic Outlook; World Economic Outlook ;, 2019)
Global growth is forecast at 3.0 percent for 2019, its lowest level since 2008-09 and a 0.3 percentage point downgrade from the April 2019 World Economic Outlook.